Implementation of a Reporting Application for the Testing Process and Results of Furniture Product at XYZ Company - Pasaribu, Faizal Asrul; Simangunsong, Jumadi; Hutagaol, Nindhia (Sistemasi: Jurnal Sistem Informasi, 2025)
The current development of the furniture industry is becoming increasingly competitive and demands a more efficient and systematically documented product testing process. This study aims to design and develop an online-based information system for reporting the testing process and results of furniture products at XYZ Company. The development method used is prototyping, which allows for iteration and continuous improvement based on user feedback. The results indicate that this application can enhance the quality of data recording for tests, making it more structured, minimizing potential human errors, and accelerating the reporting process. Therefore, XYZ Company is recommended to continue developing application features, including integration with artificial intelligence technology for predictive quality analysis, as well as implementing higher data security standards to ensure the sustainability of innovation in the long term.